Comparative in vitro exoenzyme-suppressing activities of azithromycin and other macrolide antibiotics against Pseudomonas aeruginosa. - Mizukane, R (1994)
The inhibitory effects of azithromycin (AZM), a new 15-membered macrolide antibiotic, on the production of exotoxin A, total protease, elastase, and phospholipase C by Pseudomonas aeruginosa were determined, and the virulence-suppressing effects of AZM were compared with those of erythromycin (EM), roxithromycin (RXM), and rokitamycin (RKM). The effect of exposure of P. aeruginosa PA103 or B16 in cultures to sub-MICs of these macrolide antibiotics on the production of exoenzymes was determined. AZM suppressed the in vitro production of extracellular and intracellular exotoxin A by P. aeruginosa PA103 more than did EM, even at a concentration of only 2 micrograms/ml. At concentrations of between 4 and 32 micrograms/ml, AZM also inhibited total protease, elastase, and phospholipase C production by P. aeruginosa B16 more than did EM, RXM, and RKM. AZM was effective in suppressing exotoxin A and total protease production through 24 h of incubation in the presence of drug at sub-MICs, but it had no significant effect on either the growth of P. aeruginosa or its total protein production. Moreover, at a concentration of 4 micrograms/ml, AZM suppressed exoenzyme production by other strains of P. aeruginosa more than did EM. These findings indicate that AZM, EM, RXM, and RKM each has an inhibitory effect on exoenzyme production separate from the antimicrobial effect and that, of these macrolides, AZM has the strongest virulence-suppressing effect.